The craft of oblivion : forgetting and memory in ancient China - Galvany, Albert (Albany, NY : State University of New York Press, 2023)
"Examines the intersections between forgetting and remembering in classical Chinese civilization"--
Introduction / Albert Galvany -- Part I. Historiographical and Political Narratives : Chapter 1. Cultural Amnesia and Commentarial Retrofitting: Interpreting the Sping and Autumn / Newell Ann Van Auken -- Chapter 2. Elision and Narration: Remembering and Forgetting in Some Recently Unearthed Historiographical Manuscripts / Rens Krijgsman -- Chapter 3. Shaping the Historian's Project: Language of Forgetting and Obliteration in the Shiji / Esther Sunkyung Klein -- Chapter 4. The Ice of Memory and the Fires of Forgetfulness: Traumatic Recollections in the Wu Yue chunqiu / Olivia Milburn -- Part II. Philosophical Writings : Chapter 5. The Daode jing's Forgotten Forebear: The Ancestral Cult / K.E. Brashier -- Chapter 6. So Comfortable You'll Forget You're Wearing Them: Attention and Forgetting in the Zhuangzi and Huainanzi / Franklin Perkins -- Chapter 7. The Practice of Erasing Traces in the Huainanzi / Tobias Benedikt Zürn -- Chapter 8. The Oblivious against the Doctor: Pathologies of Remembering and Virtues of Forgetting in the Liezi / Albert Galvany -- Chapter 9. Wang Bi and the Hermeneutics of Actualization / Merceded Valmisa -- Part III. Ritual and Literary Texts : Chapter 10. Embodied Memory and Natural Forgetting in Early Chinese Ritual Theory / Paul Nicholas Vogt -- Chapter 11. Exile and Return: Oblivion, Memory, and Nontragic Death in Tomb-Quelling Texts from the Eastern Han Dynasty / Xiang Li -- Chapter 12. Lost in Where We Are: Tao Yuanming on the Joys of Forgetting and the Worries of Being Forgotten / Michael D. K. Ing.
Includes bibliographical references and index.
Albert Galvany Associate Professor of Philosophy at the University of the Basque Country UPV/EHU.
Print version record.
JSTOR
Keywords: China -- Civilization -- To 221 B.C. -- Sources; China -- Civilization -- 221 B.C.-960 A.D. -- Sources; Chinese literature -- To 221 B.C. -- History and criticism; Chinese literature -- 221 B.C.-960 A.D. -- History and criticism; Philosophy, Chinese -- To 221 B.C.; Philosophy, Chinese -- 221 B.C.-960 A.D.; Memory; Chine -- Civilisation -- Jusqu'à 221 av. J.-C. -- Sources; Chine -- Civilisation -- 221 av. J.-C.-960 -- Sources; Littérature chinoise -- Jusqu'à 221 av. J.-C. -- Histoire et critique; Littérature chinoise -- 221 av. J.-C.-960 -- Histoire et critique; Philosophie chinoise -- Jusqu'à 221 av. J.-C.; Philosophie chinoise -- 221 av. J.-C.-960.; HISTORY / Asia / China; Chinese literature; Civilization; Memory; Philosophy, Chinese; China; To 960; Criticism, interpretation, etc; Sources